Highly Sensitive Heavy Metal Ion Detection Using AlQ3 Microwire Functionalized QCM - Can, Nursel; Agar, Meltem; Altindal, Ahmet (AMER INST PHYSICS, 2016)
Tris(8-hydroxyquinoline) aluminum (Alq(3)) microwires was successfully synthesized for the fabrication of Alq3 microwires-coated QCM sensors to detect the heavy metal ions in aqueous solution. AT-cut quartz crystal microbalance (QCM) of 10 MHz fundamental resonance frequency having gold electrodes were used as transducers. Typical measuring cycle consisted of repeated flow of target measurands through the flow cell and subsequent washing to return the baseline. The QCM results indicated that the Alq(3) microwires exhibit excellent sensitivity, stability and short response-recovery time, which are much attractive for the development of portable and highly sensitive heavy metal ion sensors in water samples.
Keywords: LEAD; MERCURY; COPPER; WATER; Physics